Methamphetamine-type stimulant use in Lao PDR: Qualitative findings from users aged 15-25 years in Vientiane Capital and Vientiane Province - Vanphanom Sychareun (2018)
© 2018 The Author(s). Background: Methamphetamine is one of the most widely used illicit drugs in several Southeast Asian countries, including the Lao People's Democratic Republic (PDR). The purpose of this study was to examine the socio-cultural context of its use in Lao PDR. Methods: We conducted a cross-sectional qualitative survey among young people, aged 15-24 years, who use methamphetamine (or Yaba as it is commonly known in the region) in Vientiane Capital and Vientiane Province, Lao PDR. In total, we conducted 21 in-depth interviews (6 female, 13 males and 2 transgender) and 8 focus group discussions with 47 participants (10 female, 29 male and 8 transgender). The data analysis drew on the theory and insights of the social theorist Pierre Bourdieu (1990, 1997) to understand the Yaba consumption practices among young Laotians. Results: Yaba consumption among young people in this study was used to enhance both productivity and pleasure. Its pleasure-producing affects were often linked to core Laotian notions of having fun, partying and being together. Its increased productivity effects on the other hand, were used to pursue goals related to self-betterment within an emerging market economy. Conclusions: This study highlights the complex interaction between agency and identity, structure, context and practices. In terms of public health policy and programme responses, developing proper interventions implies a good understanding of how young people interpret Yaba consumption, its dynamics and the relationships and resources that mediate the behaviours.